Your dissertation in education - Walliman, Nicholas S. R.; Buckler, Scott (Los Angeles SAGE, 2008)
A practical step-by-step guide to managing and developing a successful undergraduate project.
Part one : introduction to the dissertation process. What is a dissertation? ; What is educational research? ; What's all this about ethics? -- Part two : establishing a focus. What will it be about? ; How do I get started? ; How do I write a proposal? ; How do I write an introduction? -- Part three : exploring the background to the topic. Where so I get hold of all the necessary background information? ; How can I manage all the notes? ; What about referencing? ; How do I argue my point effectively? ; How do I write a literature review? -- Part four : conducting the research. What sorts of data will I find and how much do I need? ; What's all this about philosophy? ; How do I conduct effective interviews? ; How do I structure effective questionnaires? ; How do I undertake effective observations? ; How do I write a methodology chapter? -- Part five : analyzing the data and identifying conclusions. How do I analyze quantitative data? ; How do I analyze qualitative data? ; How do I write a discussion chapter? -- Part six : practical guidance on the subject. How can I work effectively with my supervisor? ; What about working and planning my time? ; How can I manage a long piece of writing? ; How can I make my work look interesting and easy to read? ; How do I cope with stress? ; Who else might be interested in my writing?
Updated ed. of: Your undergraduate dissertation : the essential guide for success / Nicholas Walliman.
Keywords: Education -- Research -- Methodology; Dissertations, Academic; Academic writing